RELATIONSHIP BETWEEN ACADEMIC SELF-CONCEPT IN SCIENCE AND COGNITIVE PREFERENCE STYLES - Padhi, J.S. (SCHOOL SCIENCE, 2013)
The study aims at finding the relationship between Cognitive Preference Styles (CPS) and Academic Self-concept in Science (ASCSc) of the secondary school students. The sample consisted of 200 Class IX students. The study reveals that ‘Application’ style is positively and significantly related to ASCSc. Students differ in their CPS with high and low ASCSc; and gender differences are absent in CPS.